PENGARUH ATRIBUT KUALITAS TERHADAP KEPUTUSAN PEMBELIAN MI CEPAT SAJI - Rofi’ah, Ainur; Mardhiyyah, Yunita Siti (Jurnal Agroindustri, 2023)
Cepat sajit noodles are a processed food product as energy sources that are popular in Indonesia. The existence of the “Pilihan Lebih Sehat” logo issued by BPOM in 2019 on pasta and cepat sajit noodles, provides another alternative in product selection by consumers. This study aims to assess the quality factors of cepat sajit noodle products (health claims, performance, aesthetics, and conformance quality) to purchasing decisions. Four exogenous variables, X1 for health claims, X2 for performance, X3 for conformity, and X4 aesthetics were analysed using The Partial Least Square (PLS) method. Thus, the purchase decision (Y) as endogenous variable were analysed from 2 types of noodle samples, namely the “A” and “B” brands, the two big brands of cepat sajit noodle with “mi goreng” flavor. A total of 100 respondents in each sample of noodles had filled out an online questionnaire. The results showed that “B” noodles received higher purchase decision assessment than “A” noodles, which was 3.86 against 3.71 on scale of 1 to 5. All exogenous variables had a positive and significant effect on “A”'s purchasing decision. In “B”, all variables except X1 had a positive and significant effect. Indonesian consumers still tend to prioritize the quality of performance (taste, texture, color, aroma) and the quality of conformity related to price and weight, especially in “B” noodle products. Going forward, adhering the BPOM’s health claims will give added value of products and may increase the market of innovate cepat sajit noodle products.